2004
DOI: 10.1128/iai.72.9.5292-5297.2004
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Protection against Porcine Cysticercosis by Vaccination with Recombinant Oncosphere Antigens

Abstract: Two recombinant Taenia solium oncosphere antigens, designated TSOL18 and TSOL45-1A, were investigated as vaccines to prevent transmission of the zoonotic disease cysticercosis through pigs. Both antigens were effective in inducing very high levels of protection (up to 100%) in three independent vaccine trials in pigs against experimental challenge infection with T. solium eggs, which were undertaken in Mexico and Cameroon. This is the highest level of protection that has been achieved against T. solium infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
146
2
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 34 publications
4
146
2
7
Order By: Relevance
“…Two different T. solium recombinant oncosphere proteins (Tsol18 and Tsol45) have been tested and shown to be highly effective in protecting pigs against cysticercosis [14,15]. Both proteins plus a third, Tsol16, have been identified and cloned by homology to the T. ovis and T. saginata protective antigens [26;27;].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different T. solium recombinant oncosphere proteins (Tsol18 and Tsol45) have been tested and shown to be highly effective in protecting pigs against cysticercosis [14,15]. Both proteins plus a third, Tsol16, have been identified and cloned by homology to the T. ovis and T. saginata protective antigens [26;27;].…”
Section: Discussionmentioning
confidence: 99%
“…The essential role of pigs as obligatory intermediate hosts presents a possibility of interfering with transmission of both diseases (taeniasis and cysticercosis) through vaccination of pigs. To date, oncosphere antigens are the most effective vaccine candidates in preventing cysticercosis [10][11][12][13][14][15]. We identified two oncosphere protein bands in western blot that were associated with immune protection against cysticercosis in pigs [12].…”
Section: Introductionmentioning
confidence: 97%
“…El grupo de parasitología veterinaria de la Universidad de Melbourne, Australia, encabezado por el Dr. Marshall Lightowlers, desarrolló una vacuna altamente eficaz para la cisticercosis porcina, probada inicialmente en México, Camerún y Perú a inicios de la primera década del 2000. Esta vacuna, llamada TSOL18, tiene una eficacia superior al 99% y fue desarrollada siguiendo el esquema de vacunas similares contra Taenia ovis y Taenia saginata (30,31) .…”
Section: Control En Camalesunclassified
“…TSOL18 has been assessed in five separate pig vaccine trials, under experimental conditions conducted by four independent groups of scientists in four different countries. In the challenge trials, TSOL18 consistently provided vaccinated pigs with nearly complete protection against T. solium infection, achieving 100% and 99.5% protection in Mexico, 13 99.9% in Peru, 15 100% in Cameroon 13 and 99.3% in Honduras. 16 In addition, the TSOL18 antigen was shown to completely eliminate transmission of T. solium to pigs in a vaccine field trial conducted in the Mayo-Danay district of north Cameroon, 17 a region previously identified as having a high prevalence of T. solium.…”
mentioning
confidence: 99%
“…12 Each of these antigens has been shown to induce near complete protection in vaccinated pigs challenged with T. solium under experimental conditions. [13][14][15] The TSOL18 antigen has shown the greatest potential. TSOL18 has been assessed in five separate pig vaccine trials, under experimental conditions conducted by four independent groups of scientists in four different countries.…”
mentioning
confidence: 99%